Путівники Львовом (друга половина ХIХ – початок ХХI ст.): ретроспективний огляд - Мовна, М. В. (Видавництво Львівської політехніки, 2015)
Розглянуто історію створення путівників Львовом. У контексті розгляду історії становлення та подальшого розвитку путівника львівські вадемекуми класифіковано на шість хронологічних періодів (австрійський, російський, польський, радянський, німецький, український), визначено типологічну належність путівників, підкреслено їх тематичне, ідеологічне та лінгвістичне розмаїття. This article considers some points in the history of Lviv city guides. The publication presents the classification of Lviv vade-mecums in the context of reviewing history of city guides formation and its further development as the genre of reference and informational issues, which include sic chronological periods (Austrian, Russian, Polish, Soviet, German and Ukrainian), defines the typological affiliation of city guides and accentuates their thematic, ideological and linguistic variety.
Lviv guide books (from the second half of the 19th century to early 21th century): retrospective review
Keywords: путівник; вадемекум; Львів; історія; ретроспективний огляд; guide book; Lviv; history; retrospective review